Isotopic insights into the fate of atmospheric nitrogen in alpine tundra ponds with contrasting land cover and cryospheric conditions - R. Balestrini; N. Colombo; M. Freppaz; M.F. Lehmann; C. Delconte; E. Pintaldi; F. Salerno; I. Matiatos (CATENA, 2026)

Treatment of veterinary insecticide residues using biomixtures: performance, degradation kinetics, and ecotoxicological assessment - R. C. Pessagno; N. Olié; V. A. Silvani; R. P. Colombo; G. Svartz; A. Iriel (International Journal of Environmental Science and Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Perspectives on abiotic ecosystem services provided by glacial lakes in high-mountain areas - C. Viani; N. Colombo; M. Rogora; M. Giardino; M. Freppaz; I.M. Bollati (Ecosystem Services, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Evidence of a large igneous province at ca. 347–330 Ma along the northern Gondwana margin linked to the assembly of Pangea: Insights from U–Pb zircon geochronology and geochemistry of the South-Western Branch of the Variscan Belt (Morocco) - Oussama Moutbir; El Mostafa Aarab; Nasrrddine Youbi; Abdelhak Ait Lahna; Colombo Celso Gaeta Tassinari; João Mata; Ross N. Mitchell; Andreas Gärtner; Alvar Soesoo; Mohamed Khalil Bensalah; Abderrahmane Soulaimani; Moulay Ahmed Boumehdi; et al. (Earth-Science Reviews, 2024)

Low prevalence of microplastic contamination in the bottom sediments and deep-sea waters of the Bransfield strait, Antarctica - Gabriel Enrique De-la-Torre; Ana D. Forero López; Carolina V. Colombo; Guido N. Rimondino; Fabio E. Malanca; Martha Barahona; Luis Santillán (Chemosphere, 2024)

High-Resolution In Situ Characterization of the Hydrochemical Variability Along the Fluvio-marine Transition of the Río de la Plata Estuary, Argentina - S. Heguilor; E. D. Speranza; L. M. Tatone; C. N. Skorupka; M. C. Migoya; J. C. Colombo (Estuaries and Coasts, 2024)

High-resolution temporal variations of nitrate in a high-elevation pond in alpine tundra (NW Italian Alps) - N. Colombo; R. Balestrini; D. Godone; D. Vione; D. Said-Pullicino; G. Viviano; M. Martin; C.A. Delconte; S. Fratianni; A.G. Capodaglio; E. Pintaldi; M. Freppaz; et al. (CATENA, 2024)

OS04-02: Next Generation PBK modeling with PK-Sim for the prediction of chemical distribution in humans - R. Geci; D. Gadaleta; S. Proença; E. Colombo; M. García de Lomana; R. Ortega Vallbona; N. Kramer; A. Paini; L. Küpfer; S. Schaller (Toxicology Letters, 2023)

Psilocybin prevents reinstatement of alcohol seeking by disrupting the reconsolidation of alcohol-related memories - F. Benvenuti; D. Colombo; L. Soverchia; N. Cannella; E. Domi; R. Ciccocioppo (Psychopharmacology, 2023)

Hydrological, thermal and chemical influence of an intact rock glacier discharge on mountain stream water - F. Bearzot; N. Colombo; E. Cremonese; U. Morra di Cella; E. Drigo; M. Caschetto; S. Basiricò; G.B. Crosta; P. Frattini; M. Freppaz; P. Pogliotti; F. Salerno; et al. (Science of The Total Environment, 2023)

Stratigraphy and tectosedimentary evolution of the late Paleozoic Ancestral Andes between 33° and 25° SL - Carlos O. Limarino; Nemesio Heredia; Luis A. Spalletti; Pedro Busquets; Ferrán Colombo; Isabel Méndez-Bedia; Raúl Cardó; Silvia N. Césari (Journal of South American Earth Sciences, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Molecular Identification and Antimicrobial Activity of Foliar Endophytic Fungi on the Brazilian Pepper Tree (Schinus terebinthifolius) Reveal New Species of Diaporthe - Germana D. dos Santos; Renata R. Gomes; Rosana Gonçalves; Gheniffer Fornari; Beatriz H. L. N. S. Maia; Claudia Schmidt-Dannert; Francois Gaascht; Chirlei Glienke; Gabriela X. Schneider; Israella R. Colombo; Juliana Degenhardt-Goldbach; João L. M. Pietsch; et al. (Current Microbiology, 2021)

The use of biomimetic tools for water quality monitoring: passive samplers versus sentinel organisms - M. Morrone; N. E. Cappelletti; L. M. Tatone; M. J. Astoviza; J. C. Colombo (Environmental Monitoring and Assessment, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Zootechnical performance, biochemical response, and chromaticity in Pacific white shrimp (Litopenaeus vannamei) (Boone, 1931) after the inclusion of lyophilized açaí (Euterpe oleracea) in the diet - Shadai M. Silva; Patricia B. Ramos; Juan R. Buitrago; Thamyres V. N. da Silva; Cleber S. Simião; Grecica M. Colombo; Marcos Schmitz; Marcelo B. Tesser; Carlos Prentice; Wilson Wasielesky; José M. Monserrat (Aquaculture International, 2020)

Correction to: Psychiatric disorders and SLC6A4 gene variants: possible effects on alcohol dependence and alzheimer’s disease - Marco Calabrò; Laura Mandelli; Concetta Crisafulli; Stefano Porcelli; Diego Albani; Antonis Politis; George N. Papadimitriou; Marco Di Nicola; Luigi Janiri; Roberto Colombo; Giovanni Martinotti; Antonello Bellomo; et al. (Molecular Biology Reports, 2020)

Psychiatric disorders and SLC6A4 gene variants: possible effects on alcohol dependence and alzheimer’s disease - Marco Calabrò; Laura Mandelli; Concetta Crisafulli; Stefano Porcelli; Diego Albani; Antonis Politis; George N. Papadimitriou; Marco Di Nicola; Luigi Janiri; Roberto Colombo; Giovanni Martinotti; Antonello Bellomo; et al. (Molecular Biology Reports, 2020)

Coupled Modeling of Sedimentary Basin and Geomechanics: A Modified Drucker–Prager Cap Model to Describe Rock Compaction in Tectonic Context - N. Guy; D. Colombo; J. Frey; T. Cornu; M. C. Cacas-Stentz (Rock Mechanics and Rock Engineering, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Beneficial and Safety Properties of a Corynebacterium vitaeruminis Strain Isolated from the Cow Rumen - M. Colombo; N. P. A. Castilho; S. D. Todorov; L. A. Nero (Probiotics and Antimicrobial Proteins, 2017)

Fatty acid alterations in the detritivorous Prochilodus lineatus promoted by opportunistic feeding on sewage discharges in the R ío de la P lata estuary - E. D. Speranza; M. Colombo; L. M. Tatone; N. Cappelletti; M. C. Migoya; J. C. Colombo (Journal of Fish Biology, 2016)
Muscle fatty acid profiles and PCB contents of the detritivorous species Prochilodus lineatus and its diet (stomach contents, settling particles and sediments) were analysed from reference and polluted areas of the Paraná‐Rio de la Plata basin, to evaluate the alterations produced by opportunistic feeding on sewage discharges. Overall muscle fatty acid composition was dominated by saturated and monounsaturated 16 and 18 carbon (18 C‐ FA ) components with reduced long‐chain polyunsaturated fatty acids ( LC‐PUFA ). Compared to sediments, settling particles and stomach contents were enriched in lipids and had a similar fatty acid composition. Opportunistic feeding on sewage detritus at Buenos Aires resulted in enhanced PCB and triglyceride accumulation, with higher proportions of 18 C‐ FA and lower proportions of 16:1 and LC‐PUFA compared to fish from northern pristine reaches of the basin. Mid‐Paraná showed intermediate values reflecting mixing of the North stock with migrating Buenos Aires P. lineatus identified by their lipid and contaminant profile. According to multivariate analyses, this geographical variation of fatty acid composition was strongly influenced by PCB concentration. Prochilodus lineatus assimilates the energy subsidy of sewage inputs through enhanced lipogenesis with dominant 18 C‐ FA and significant amounts of valuable LC‐PUFA . This lipid alteration facilitates the bioaccumulation of PCBs which in turn may reinforce the adipogenic effect of sewage feeding.

Seasonal and inter-annual variability of water quality in the Uruguay River, Argentina - Juan C. Colombo; Carlos N. Skorupka; Claudio Bilos; Leandro Tatone; Natalia Cappelletti; M. Carolina Migoya; Malena Astoviza; Eric Speranza (Hydrological Sciences Journal, 2015)

Timing of multiple hydrothermal events in the iron oxide–copper–gold deposits of the Southern Copper Belt, Carajás Province, Brazil - Carolina P. N. Moreto; Lena V. S. Monteiro; Roberto P. Xavier; Robert A. Creaser; S. Andrew DuFrane; Gustavo H. C. Melo; Marco A. Delinardo da Silva; Colombo C. G. Tassinari; Kei Sato (Mineralium Deposita, 2015)

Bioaccumulation of dioxin-like PCBs and PBDEs by detritus-feeding fish in the Rio de la Plata estuary, Argentina - N. Cappelletti; E. Speranza; L. Tatone; M. Astoviza; M. C. Migoya; J. C. Colombo (Environmental Science and Pollution Research, 2015)

Behavior of Dioxin Like PCBs and PBDEs During Early Diagenesis of Organic Matter in Settling Material and Bottom Sediments from the Sewage Impacted Buenos Aires’ Coastal Area, Argentina - N. Cappelletti; C. N. Skorupka; M. C. Migoya; L. Tatone; M. Astoviza; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2014)

Effects of Nicotine on Cardiovascular Remodeling in a Mouse Model of Systemic Hypertension - E. Sage Colombo; Joshua Davis; Mehran Makvandi; Mario Aragon; Selita N. Lucas; Michael L. Paffett; Matthew J. Campen (Cardiovascular Toxicology, 2013)

The relationship between carbonate facies, volcanic rocks and plant remains in a late Palaeozoic lacustrine system (San Ignacio Fm, Frontal Cordillera, San Juan province, Argentina) - P. Busquets; I. Méndez-Bedia; G. Gallastegui; F. Colombo; R. Cardó; O. Limarino; N. Heredia; S. N. Césari (International Journal of Earth Sciences, 2013)

Trace Metals in Settling Particles from the Sewage Impacted Buenos Aires Coastal Area in the Río de la Plata Estuary, Argentina - L. M. Tatone; C. Bilos; C. N. Skorupka; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2013)

Migratory behaviour of a dominant detritivorous fish Prochilodus lineatus evaluated by multivariate biochemical and pollutant data - E. D. Speranza; N. Cappelletti; M. C. Migoya; L. M. Tatone; J. C. Colombo (Journal of Fish Biology, 2012)
This paper studies the migration pathways and ranges of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Río de la Plata basin using multivariate analysis of biochemical and pollutant data. Biochemical composition (water, ash, lipids, proteins, carbohydrates, neutral lipids classes and fatty acids), aliphatic hydrocarbons (ALI), polychlorinated biphenyls (PCB), linear alkylbenzenes (LAB) and organochlorine pesticides (OClP) were determined in muscle samples of P. lineatus collected in Metropolitan Buenos Aires, the lower Paraná River (Paraná: 200–1000 km from Buenos Aires) and the middle Paraná and Paraguay Rivers (North: 1000–1400 km north). Biochemical variables and pollutants exhibited large variability [Lipids 1·1–89·5% wet mass; ALI 1·4–413; LABs not detectable (n.d.)–115·2; PCBs n.d.–27·9; OClPs n.d.–11·8 µg g −1 dry mass], due to the contrast of Buenos Aires with North fish. Fish from Buenos Aires were fatty (lipids 24·7 ± 12·3% wet mass), enriched in 18 carbon fatty acids and severely contaminated (ALI 152·4 ± 72·3; LABs 65·1 ± 26·4; PCBs 15·2 ± 6·8; OClPs 1·8 ± 1·9 µg g −1 dry mass mean ± s.d .). In contrast, fish from North were lean (4·1 ± 3·1% wet mass), enriched in long chain (>20 carbons) polyunsaturated fatty acids, with average one to two orders of magnitude lower pollutant levels (ALI 41·2 ± 51·9; PCBs 2·2 ± 3·5; LABs 8·8 ± 21·1; OClPs 0·67 ± 0·75 µg g −1 dry mass mean ± s.d .). Paraná showed intermediate values in all variables, denoting the mixing of different fish stocks. Based on principal component analysis, 14 outliers from 60 North and Paraná samples (representing 26 from 108 individual fish) were identified as pertaining to the Buenos Aires group with very similar lipid and pollutant levels. Data suggest that P. lineatus migrates a highly variable distance, exceeding 800–1000 km in multiple spatial and temporal overlapping ranges. Chemometric analysis of biochemical and pollutant data effectively discriminates fish according to the chemical signature acquired by detritus feeding in pristine and contaminated urban or industrial areas.

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

With time on our side? Task-dependent compensatory processes in graceful aging - M. Berlingeri; G. Bottini; L. Danelli; F. Ferri; D. Traficante; L. Sacheli; N. Colombo; M. Sberna; R. Sterzi; G. Scialfa; E. Paulesu (Experimental Brain Research, 2010)

Vertical Fluxes and Accumulation of Trace Metals in Superficial Sediments of the Río de la Plata Estuary, Argentina - L. M. Tatone; C. Bilos; C. N. Skorupka; J. C. Colombo (Bulletin of Environmental Contamination and Toxicology, 2009)

Global Distribution and Outcomes for Candida Species Causing Invasive Candidiasis: Results from an International Randomized Double-Blind Study of Caspofungin Versus Amphotericin B for the Treatment of Invasive Candidiasis - A. L. Colombo; J. Perfect; M. DiNubile; K. Bartizal; M. Motyl; P. Hicks; R. Lupinacci; C. Sable; N. Kartsonis (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

The sea beet (Beta vulgaris L. ssp.maritima) of the adriatic coast as source of resistance for sugar beet - Piergiorgio Stevanato; Marco De Biaggi; George N. Skaracis; Mauro Colombo; Giuseppe Mandolino; Enrico Biancardi (Sugar Tech, 2001)

Genomic changes in transgenic rice (Oryza sativa L.) plants produced by infecting calli with Agrobacterium tumefaciens - M. Labra; C. Savini; M. Bracale; N. Pelucchi; L. Colombo; M. Bardini; F. Sala (Plant Cell Reports, 2001)